2020
DOI: 10.1038/s41598-020-78858-2
|View full text |Cite
|
Sign up to set email alerts
|

Fresh water skin disease in dolphins: a case definition based on pathology and environmental factors in Australia

Abstract: A distinct ulcerative dermatitis known as “freshwater skin disease” is an emerging clinical and pathological presentation in coastal cetaceans worldwide. In Australia, two remarkably similar mortality events enabled the creation of a case definition based on pathology and environmental factors. The first affected a community of endemic Tursiops australis in the Gippsland Lakes, Victoria, while the second occurred among T. aduncus resident in the Swan-Canning River system, Western Australia. The common features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 57 publications
2
24
0
1
Order By: Relevance
“…For each dolphin in June and September 2017, veterinarians conducted a skin assessment using a standardized form to document the location and description of each lesion type (Supplemental Materials). Visual assessment of freshwater-like lesions was typically characterized by hypopigmented, circular and/or irregular, multifocal to coalescing lesions and may or may not have had associated ulcerations and were consistent with freshwater lesions described in other studies [ 13 , 14 ]. Two experienced researchers (LS and CS) reviewed photographs of each dolphin to confirm the presence or absence of freshwater-like lesions.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…For each dolphin in June and September 2017, veterinarians conducted a skin assessment using a standardized form to document the location and description of each lesion type (Supplemental Materials). Visual assessment of freshwater-like lesions was typically characterized by hypopigmented, circular and/or irregular, multifocal to coalescing lesions and may or may not have had associated ulcerations and were consistent with freshwater lesions described in other studies [ 13 , 14 ]. Two experienced researchers (LS and CS) reviewed photographs of each dolphin to confirm the presence or absence of freshwater-like lesions.…”
Section: Methodssupporting
confidence: 81%
“…Our results have applicability to Southeastern U.S. bottlenose dolphin stocks, as well as marine mammal populations/species worldwide that have long-term site fidelity and limited ranging patterns to a given habitat. For example, dolphins in Australia ( Tursiops aduncus and Tursiops australis ) exhibited similar skin lesions after sudden and weeks/months-long exposure to hypo-saline conditions due to intense rainfall [ 13 ]. Indo-Pacific humpback dolphins ( Sousa chinensis ) in China and Taiwan [ 81 83 ] and the Chilean and Guinean dolphins ( Cephalorhynchus eutropia and Sotalia guianensis , respectively) in South America [ 84 , 85 ] are also species/populations that are impacted by many of the same environmental stressors as Barataria dolphins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other cetaceans exposed to fresh water for an extended period (e.g., Priddel and Wheeler, 1997), killer whales in Nushagak River (and Barnes Lake) had a skin condition characterized by severe degenerative changes caused by fungal and bacterial overgrowth (Bain, 1995;Raverty et al, 2020). Such compromised condition, known to have lethal consequences in cetaceans (Duignan et al, 2020), was confirmed to have contributed to mortality in this specific case (Raverty et al, 2020).…”
Section: Lethality Of Killer Whale Entrapmentssupporting
confidence: 59%
“…Dolphins are physiologically adapted to inhabit brackish to oceanic coastal waters with salinities that typically range from 15 to 35 ppt (Ewing et al, 2017;McClain et al, 2020;Booth and Thomas, 2021). Those that remain in an area subject to a low salinity event may suffer from freshwater intoxication due to oral ingestion and/or skin absorption, leading to serious negative health consequences (Ewing et al, 2017;Deming et al, 2020;Duignan et al, 2020;Fazioli and Mintzer, 2020;McClain et al, 2020;McBride-Kebert and Toms, 2021). Effects of freshwater exposure on dolphins can include development of hydropic degeneration and ulcerative or erosive skin lesions (e.g., Wilson et al, 1999;Mullin et al, 2015;Duignan et al, 2020;Fazioli and Mintzer, 2020;McClain et al, 2020;Toms et al, 2020;Townsend, 2020;Takeshita et al, 2021), corneal edema (Deming et al, 2020), and changes in blood chemistry and electrolytes (Ewing et al, 2017;Deming et al, 2020;McClain et al, 2020).…”
Section: Discussionmentioning
confidence: 99%